2019
DOI: 10.1108/ijilt-11-2018-0127
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the emotional impact of virtual reality-based teacher training

Abstract: The last few years Virtual Reality (VR) based approaches have emerged lately as a new education paradigm. This paper addresses the possibility to cultivate reflection and empathy skills using a VR based framework targeting to maximize the professional development of teachers. Reflection and empathy are considered to be skills of paramount importance for teachers and an integral part of their professional development. The current research aimed to investigate possible differences in cultivating reflection and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 68 publications
0
29
0
2
Order By: Relevance
“…The study suggested that the virtual learning system can improve operational skills and provide an immersive experience to students. Stavroulia et al [28] developed a VR-based teacher training system for giving the 3D virtual experience of real-life situations in the school environment. The VR training system aimed to provide a situational learning experience to teachers related to substance use among the students.…”
mentioning
confidence: 99%
“…The study suggested that the virtual learning system can improve operational skills and provide an immersive experience to students. Stavroulia et al [28] developed a VR-based teacher training system for giving the 3D virtual experience of real-life situations in the school environment. The VR training system aimed to provide a situational learning experience to teachers related to substance use among the students.…”
mentioning
confidence: 99%
“…Emotion can affect heart rate when the subject is stimulated [ 5 ]. We conducted two experiments using our method to prove that it can provide effective data support for emotion recognition.…”
Section: Methodsmentioning
confidence: 99%
“…Bland et al [4] evaluated the heart rate responses of students answering a series of questions related to the theory of evolution and found that students would produce perceptible emotional responses in the form of physiological changes when they were exposed to the theme of evolution. Stavroulia et al [5] (1) We propose a symmetry substitution method. When the head is rotated 30 degrees to 45 degrees, and the region of interest in the face is partially missing, the data detected in the left and right cheeks are symmetrically copied; (2) We designed a method to determine the effective facial region of interest (ROI) based on the face-eye location then calculate the physiological parameters;…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been showed by several studies (Groom et al, 2009;Farmer et al, 2012;Maister et al, 2013;Peck et al, 2013;Banakou et al, 2016;Behm-Morawitz et al, 2016;Hasler et al, 2017) that embodiment of light-skinned participants in a dark-skinned virtual body significantly reduced implicit racial bias against dark-skinned people. Finally, a study (Christofi et al, 2018;Stavroulia et al, 2018Stavroulia et al, , 2019 examined the effect of viewing in VR, a drug incident at a school environment from different perspectives and viewpoints in relation to the level of presence achieved and the effects on mood states and empathy of teachers who were immersed in a virtual school where a drug use incident took place.…”
Section: Introductionmentioning
confidence: 99%